Activation of the Interleukin-34 Inflammatory Pathway in Response to Influenza A Virus Infection. (February 2015) - Yu, Guozheng; Bing, Yuntao; Zhu, Siying; Li, Wei; Xia, Lin; Li, Yong; Liu, Zhisu
Abstract : Abstract: Interleukin 34 (IL-34) is a newly recognized cytokine that functions similarly to macrophage colony-stimulating factor. This study investigated the mechanism by which IL-34 is produced in response to exogenous pathogen infections in humans. The results showed that the IL-34 levels were higher in the serum and peripheral blood mononuclear cells (PBMCs) from 155 influenza A virus (IAV)-infected patients than in those from 145 healthy individuals. The expression level of IL-34 in IAV-infected PBMCs was blocked by IL-22-specific siRNA. This result indicated that IL-34 was induced by IL-22 in the inflammatory cascade. The mRNA and protein expression levels of IL-22 activated by IAV infection were significantly inhibited by IL-34 overexpression but induced by IL-34-specific siRNA. Thus, a feedback system most likely exists between IL-34 and IL-22. The IL-22 expression in T helper type 17 (Th17) cells of PBMCs was higher than IL-34 expression in Th17 cells of PBMCs, and there was IL-34 expression in IL-22+ Th17 cells. This result showed that the production of IL-22 and IL-34 is both from the same and different subset of cells, which indicated that the regulatory mechanism of IL-22/IL-34 is through the autocrine or paracrine systems. In conclusion, IL-34 is induced by IL-22 in the inflammatory cascade in response to IAV infection. Therefore, IL-34 is a promising target for the screening of anti-inflammatory medicines.